Cooperating with "Maritime India" in the Indo-Pacific context – A Japanese view. (2nd January 2020) - Tokuchi, Hideshi
ABSTRACT: The main purpose of this article is to identify a common basis for Japan and India as maritime democracies to work together for the maintenance and enhancement of the rules-based liberal international order at sea in the face of a variety of challenges in the Indo-Pacific region, China's maritime advancement in particular. As powerful maritime democracies in the Indo-Pacific, Japan and India will be able to engage in a wide variety of maritime security cooperation. The opinions of security experts of both countries should be mustered so that bilateral cooperation keeps up its momentum. Synergy of Tracks 1, 1.5 and 2 dialogues should be pursued for maritime security cooperation. In this bilateral effort, the US-centred alliance network, of which the Japan-US Alliance is the central portion, and India's autonomous and multi-directional approach toward international security must be intertwined effectively. Also, security dialogues between the two countries and between the two navies should work out the division of labour between Japan and India to contribute to the Indo-Pacific regional maritime security more effectively.